2023
DOI: 10.3390/ijerph20021261
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Going to Tell You Something I Never Told Anyone”: Ethics- and Trauma-Informed Challenges of Implementing a Research Protocol with Syrian Refugees

Abstract: As research subjects, refugees have numerous potential vulnerabilities. This study aimed to examine the ethics- and trauma-informed challenges of implementing a mental health research protocol with Syrian refugees living in Portugal. Guided by the integrated meaning-making model, the research project “Journeys in Meaning” employed a mixed-methods cross-sectional design to explore posttraumatic cognitive processing in refugees using two phases of data collection: two focus groups (Phase 1) to test the protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Some refugee scholars have performed research studies and put forward an argument for a new ethics paradigm for those who work with forced migrants. Such a paradigm would promote flexibility, ethical and ecological thinking, as well as the importance of committing to principles of social change (Dehghan & Wilson, 2019; Matos et al, 2023; Seagle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some refugee scholars have performed research studies and put forward an argument for a new ethics paradigm for those who work with forced migrants. Such a paradigm would promote flexibility, ethical and ecological thinking, as well as the importance of committing to principles of social change (Dehghan & Wilson, 2019; Matos et al, 2023; Seagle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, research interviews can be a cathartic and healing experience for individuals, providing the opportunity to describe lived experiences (Rosetto, 2014). Previous research noted that whilst follow-up protocols were often time and emotional resource-consuming, participants reported being thankful, reassured of the purpose of their contribution and had an increased sense of empowerment as they reclaimed control over the life narrative and found purpose in their suffering (Matos, 2023). In this case it will be of experiences in immigration detention, often shared for the rst time.…”
Section: Anticipated Riskmentioning
confidence: 98%
“…Principal findings suggested that: the concept of holding core beliefs that can be shattered by events appraised as cognitively discrepant appeared to reflect Syrians' understandings of their experiences; religion-informed beliefs about justice, control, safety, and aspirations of continuity, which were central appraisal lenses of the war; and the war provided a common baseline for pre-/ posttrauma investigation. Detailed Phase 1 findings are published elsewhere (Matos et al, 2023). In Phase 2 (January-May 2019), we used qualitative methodology to investigate the content of religious meaning-making experiences.…”
Section: The Present Studymentioning
confidence: 99%